Goddesses in Ramessid Egypt: representations of gender and gendered agency in the divine sphere - Scrivens, E (2019)
The gendered representation of goddesses has received little explicit analysis within Egyptology. Studies of goddesses have tended to focus on materials associated with particular deities, and scholarly conversations surrounding gender have largely concerned the experiences of living people. However, the divine sphere is a very ‘real’ aspect of a culture’s social world; to only theorise gender processes among humans is to overlook an entire realm in which those processes might also be active. This thesis interrogates the gendered agency of goddesses in the Ramessid period, as materialised in their two-dimensional representations.